Investigating effective support mounts for fans during display by exploring new technologies - Sarah Bright (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Blaise Castle House Museum in Bristol (UK) houses a large and impressive collection of 130 European fans ranging from 1700-1950 with 60 brisé and 70 other fans in a generally good condition.  This research project explored how to best support this sort of collection by using 3D fabrication technology to create bespoke mounts.  At present making mounts for fans is complex and time consuming due to the layering and structure of fans, and the need for accuracy if the mount is to support the fan sufficiently.  This project explored how creating a digital 3D image of a fan could enable 3D fabrication technologies to be used to produce an exact ‘imprint’ of the object ensuring that all areas were supported, allowing a more suitable fan display to be created.  This paper outlines the process of exploring the principles of creating mounts for fans; narrates the process of selecting suitable objects for display, and the process of creating a digitally-produced fan mount.